2013
DOI: 10.1073/pnas.1321399111
|View full text |Cite
|
Sign up to set email alerts
|

Electroconvulsive therapy-induced brain plasticity determines therapeutic outcome in mood disorders

Abstract: There remains much scientific, clinical, and ethical controversy concerning the use of electroconvulsive therapy (ECT) for psychiatric disorders stemming from a lack of information and knowledge about how such treatment might work, given its nonspecific and spatially unfocused nature. The mode of action of ECT has even been ascribed to a "barbaric" form of placebo effect. Here we show differential, highly specific, spatially distributed effects of ECT on regional brain structure in two populations: patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
127
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 172 publications
(150 citation statements)
references
References 30 publications
18
127
5
Order By: Relevance
“…This is in line with previous studies (Nordanskog et al, 2010;Tendolkar et al, 2013;Abbott et al, 2014;Dukart et al, 2014;Nordanskog et al, 2014;Bouckaert et al, 2015;Jorgensen et al, 2015;Ota et al, 2015;Sartorius et al, 2016). Only two studies found an association between hippocampal volume increase and therapeutic efficacy (Dukart et al, 2014;Joshi et al, 2015). Our data suggest that the hippocampal volume increase after ECT is transient and reverts to baseline within 6 months, even though the antidepressant effect is sustained.…”
Section: Relationship Between Depressive Symptomatology and Hippocampsupporting
confidence: 93%
See 1 more Smart Citation
“…This is in line with previous studies (Nordanskog et al, 2010;Tendolkar et al, 2013;Abbott et al, 2014;Dukart et al, 2014;Nordanskog et al, 2014;Bouckaert et al, 2015;Jorgensen et al, 2015;Ota et al, 2015;Sartorius et al, 2016). Only two studies found an association between hippocampal volume increase and therapeutic efficacy (Dukart et al, 2014;Joshi et al, 2015). Our data suggest that the hippocampal volume increase after ECT is transient and reverts to baseline within 6 months, even though the antidepressant effect is sustained.…”
Section: Relationship Between Depressive Symptomatology and Hippocampsupporting
confidence: 93%
“…Moreover, the hippocampus and brain regions that mediate emotional and cognitive regulation are anatomically connected, lending support to the role of the hippocampus in depressionrelated circuitry (Price and Drevets, 2010;Abbott et al, 2014). Several recent magnetic resonance imaging (MRI) studies have described hippocampal volume changes following ECT (Nordanskog et al, 2010;Tendolkar et al, 2013;Abbott et al, 2014;Dukart et al, 2014;Nordanskog et al, 2014;Joshi et al, 2015;Jorgensen et al, 2015;Ota et al, 2015;Bouckaert et al, 2015;Sartorius et al, 2016). Some of these studies have also addressed structural changes in other brain areas relevant to depressive disorders, such as dorsolateral prefrontal cortex, orbitofrontal cortex (Jorgensen et al, 2015), lateral temporal cortex (Bouckaert et al, 2015), caudate nucleus (Bouckaert et al, 2015), and amygdala (Tendolkar et al, 2013;Jorgensen et al, 2015;Joshi et al, 2015;Ota et al, 2015;Sartorius et al, 2016).…”
Section: Introductionmentioning
confidence: 96%
“…Although several previous research studies have shown the increase in the GM volume of HPC after ECT (Dukart et al, 2014;Jorgensen et al, 2016;Ota et al, 2015), the morphometry carried out in this study showed no significant differences between the ECT and non-ECT groups in the GM volume of all ROIs, i.e., the left and right hemi-spheres of the cerebrum and HPC. The observational durations after ECT in those previous studies [within 3 months (Dukart et al, 2014), 1 -4 weeks (Jorgensen et al, 2016), and 9.0 ± 14.6 days (Ota et al, 2015)] were shorter than that in our study (0.86 ± 1.59 years). This might be a reason for the absence of a significant difference in GM volume between the ECT and non-ECT groups in our study.…”
Section: Discussioncontrasting
confidence: 91%
“…Recent neuroimaging studies have revealed structural and functional differences in the human brain before and after an ECT series (Dukart et al, 2014;Jorgensen et al, 2016;Ota et al, 2015). Some studies have shown an increase in the GM volume of bilateral HPCs after ECT (Jorgensen et al, 2016;Ota et al, 2015); others have shown that an ECT series significantly contributes to the increase in the GM volume of the right HPC, but not to that of the left HPC (Dukart et al, 2014;Abbott et al, 2014). Moreover, recent functional magnetic resonance imaging (MRI) studies of ECT in depression have shown some laterality of neuronal connectivity of HPC.…”
Section: Introductionmentioning
confidence: 99%
“…In this population, they found only a right-sided increase, and suggested that predominant side of stimulation could be of importance. The laterality to a right sided hippocampus increase after ECT was also shown by Dukart et al (Dukart et al 2014), again suggesting a relation between side of stimulation and hippocampal volume increase. This hypothesis is not supported in our study, in which the increase in left hippocampus was more significant than in the right, despite a predominance of right unilateral treatments.…”
Section: Hippocampal Volume Increasesupporting
confidence: 71%